KEPUASAN MASYARAKAT TERHADAP PELAYANAN PUSKESMAS: KAJIAN KUALITATIF KULTUR MEDIS, STANDARISASI MUTU, KONSEP PUSKESMAS DAN RELASI DOKTER PASIEN DI KABUPATEN JEMBER - Isa Ma'rufi; Abu Khoiri; Reny Indrayani; Heri Prasetyo (Jurnal Ilmu Kesehatan Masyarakat, 2015)
The public’s satisfaction ratings of the health center services can be seen from the performance or perceived outcome compared with expectations. The general objective of this study is to assess people's satisfaction of health center services. Method is a qualitative research approach. This research was conducted in all districts in Jember, by taking 25 informants as samples for indept interview. The sampling technique to informants by using purposive sampling and snowball sampling, qualitative research instrument of this study is the researchers themselves by holding on to an open questionnaire guidelines, technical analysis is descriptive. The results of the study describe that the majority of informants (80%) say the public satisfied of the services at the health center, the issue then the people donot know what standards they are supposed to get from the service. Service to customers is a service that can be justified and balanced. In this context, services in health centers should transparently explain the standard of service flow and what will be done by the medical waiter, so the patient know about what kind of service that they would be received. The issue of quality of service is the most important thing to increase confidence in the health centers, for example in terms of service time, the average time to get a queue number about three minutes. Then the waiting time to be called about ten to thirty minutes. While the time to see a doctor about five minutes. And the time to stand in line to take drugs in about thirtyminutes. With the size of this time, the average patient takes about one to one and a half hours in a health center. Keywords: The satisfaction of the public, health center services, medical culture and standardization quality.